2019
DOI: 10.1097/md.0000000000017312
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and etiology of repeat infection in kidney transplant recipients

Abstract: Kidney transplantation (KT) is the best therapy available for patients with end-stage renal disease, but postoperative infections are a significant cause of mortality.In this retrospective study the frequency, risk factors, causative pathogens, and clinical manifestations of infection in KT recipients from Beijing Chao-Yang Hospital, Capital Medical University were investigated. Ninety-seven KT recipients who were hospitalized with infection between January 2010 and December 2016 were included. Clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The reason for the high early UTI incidence may be that the medical staff still need to improve in the early prevention and treatment of UTIs after kidney transplantation, such as in their theoretical knowledge, patient monitoring, and patient education. Our study showed that the median time of early-stage UTI was 5 [4,10] days after surgery. This finding indicates that 4-10 days after kidney transplantation is a critical period for preventing UTI.…”
Section: Incidence and Occurrence Time Of Early Uti After Kidney Transplantationmentioning
confidence: 69%
See 2 more Smart Citations
“…The reason for the high early UTI incidence may be that the medical staff still need to improve in the early prevention and treatment of UTIs after kidney transplantation, such as in their theoretical knowledge, patient monitoring, and patient education. Our study showed that the median time of early-stage UTI was 5 [4,10] days after surgery. This finding indicates that 4-10 days after kidney transplantation is a critical period for preventing UTI.…”
Section: Incidence and Occurrence Time Of Early Uti After Kidney Transplantationmentioning
confidence: 69%
“…The recipient and graft survival rates are higher than 90% at 1 year after kidney transplantation (10). However, the survival of both recipient and graft still face many risks, among which UTI is the most common postoperative infectious complication (11).…”
Section: Incidence and Occurrence Time Of Early Uti After Kidney Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…ere is a trend for the Emergency Department to handle more previously inpatient cares. e increased importance of the Kidney Transplantation Department indicates that Kidney Transplantation is becoming a mainstream medical service and repeated infection after kidney transplantation is an urgent medical issue in outpatient clinics [18].…”
Section: E Medical Value To Study the Distribution Of Specimen Submitted Between Different Outpatient Clinics And Emergency Departmentmentioning
confidence: 99%
“…The mortality rates in kidney transplant recipients (KTR) are approximately 8.6% within the five years of the transplantation. Among them, 53% are secondary to an infection elsewhere in the body [1]. The incidence of urinary tract infection (UTI) in the renal transplant recipients accounts for 45-72% of all the infections.…”
Section: Introductionmentioning
confidence: 99%